Irritant contact dermatitis caused by needle-like calcium oxalate crystals, raphides, in Agave tequilana among workers in tequila distilleries and agave plantations - Salinas, M.L.; Ogura, T.; Soffchi, L.
It was found that needle-like calcium oxalate crystals, raphides, are found abundantly in all tissues of Agave tequilana plants; thus, 1 droplet (0.03 ml)of juice pressed from leaves contains 100-150 crystals, 30-500 mm in length, sharpened at both ends. In tequila distilleries, 5/6 of the workers who handle the agave stems have experienced the characteristic irritation. In contrast, only 1/3 of workers in agave plantations who harvest agave plants, complain of the irritation. It is confirmed that all the irritation suffered in both distilleries and plantations takes place at bodily locations where the plants come into contact with the worker's skin in the course of their work.
Keywords: IRRITANT CONTACT DERMATITIS; AGAVE; RAPHIDE; CALCIUM OXALATE; OCCUPATIONAL; TEQUILA MAKING; AGAVE HARVESTING; AGRICULTURE; DISTILLERIES